2010
DOI: 10.1007/s13312-011-0094-x
|View full text |Cite
|
Sign up to set email alerts
|

Growth pattern of schoolchildren in Sagamu, Nigeria using the CDC standards and 2007 WHO standards

Abstract: The WHO references would under-diagnose under-nutrition and over-diagnose overweight/obesity in the population studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 7 publications
2
35
3
Order By: Relevance
“…The results of the present study indicated that 10% of the children are underweight in comparison to (WHO/NCHS) reference population [15], the percent of WAZ < −2SD for boys and girls less than 10 years was 11% and 5.1% respectively. Similarly, results of another study [18] reported the prevalence of underweight occurring more in boys than girls.…”
Section: Discussionmentioning
confidence: 67%
“…The results of the present study indicated that 10% of the children are underweight in comparison to (WHO/NCHS) reference population [15], the percent of WAZ < −2SD for boys and girls less than 10 years was 11% and 5.1% respectively. Similarly, results of another study [18] reported the prevalence of underweight occurring more in boys than girls.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies reported significant differences between international reference standards in various populations (Shields and Tremblay, 2010;Fetuga et al, 2011;Twells and Newhook, 2011;Mushtaq et al, 2012), and comparison of international reference standards with local reference standard also has found significant differences (Cerrillo et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Most previous studies in Low and Middle Income Countries (LMIC) have used growth centiles to model growth, with an aim to monitor growth and detect timing of growth faltering due to malnutrition by comparing child growth to set growth reference charts (Fetuga et al, 2011; Johnson et al, 2012b; Maleta et al, 2003a; Mushtaq et al, 2012; Nguyen et al, 2012; Kalanda et al, 2005; Stein et al, 2010). Of the studies from LMIC that used growth models, none modelled growth beyond 2 years of age and none of them except for the study by Johnson et al (2012b) used mixed effects modelling to fit the growth models (Olusanya & Renner, 2011; Pagezy & Hauspie, 1985; Simondon et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that have looked at child growth in low- and middle-income countries, but few have used longitudinal data, due to the limited number of longitudinal studies (Adair et al, 2009; Cameron et al, 1986; Fetuga et al, 2011; Guedes et al, 2010; Hauspie & Pagezy, 1989; Johnson et al, 2012b; Kalanda et al, 2005; Maleta et al, 2003b; Mushtaq et al, 2012; Olusanya & Renner, 2011; Pagezy & Hauspie, 1985; Simondon et al, 1992; Stein et al, 2010). …”
Section: Introductionmentioning
confidence: 99%